Geodetic surveying in Nepal - Yokoyama, Kotaro; Omura, Makoto (Journal of Nepal Geological Society, 1982)
In 1980, one quadrilateral base line and two levelling lines were set at Dana and Kerabari, central Nepal. For the determination of fault movements along M.C.T. and M.B.F. repeated surveying was planned. In this paper disposition of surveyed points and the results of the first survey are reported. The next survey is scheduled in 1984.